Review of genotoxic effects for pesticides exposure among rural community in a farming village - How, Vivien; Hashim, Zailina; Ismail, Patimah; Omar, Dzolkhifli; Mohd Tamrin, Shamsul Bahri; Md Said, Salmiah (SCIENCEDOMAIN International, 2015)
Background: Past studies have suggested that early exposure of farm children to chronic pesticides were likely to establish genotoxic risk that might lead to cancerous cell development later during their adulthood (if not repaired properly). Objective: This review aims to fill the knowledge gap concerning the genotoxic effect on the rural community in a farming village from exposure to a mixture of pesticides. Results: This review paper shows substantial evidence that farmers were vulnerable to pesticide exposure, however, limited evidence shows that children are at an increased or equivalent risk in terms of the genotoxic effect when considering their exposure to the contaminated environment. Conclusion: This paper summarizes the existing state of knowledge concerning the genotoxic effects from pesticide exposure among farmers and their children, and highlights the genotoxic effect of pesticides as a health risk for future studies.